The replication terminator protein of the gram-positive bacterium Bacillus subtilis functions as a polar contrahelicase in gram-negative Escherichia coli. - Kaul, S (1994)
The replication terminator protein (RTP) of Bacillus subtilis is a dimer with a monomeric molecular mass of 14.5 kDa. The protein terminates DNA replication at a specific binding site. Although the protein has been crystallized and its crystal structure has been solved, the lack of an in vitro replication system in B. subtilis has been a serious impediment to the analysis of the mechanism of action of this protein. We have discovered that the protein is functional in the Gram-negative bacterium Escherichia coli in vivo and in vitro. RTP blocked replication forks initiated from a ColE1 replication origin at the cognate DNA-binding site (BS3) in a polar mode. The protein did not block rolling circle replication initiated from the pT181 origin in cell extracts of Staphylococcus aureus. RTP antagonized the helicase activity of DnaB but not that of helicase II of E. coli. Thus, RTP functioned as a polar contrahelicase blocking a helicase that participates in symmetric DNA replication but it did not impede rolling circle replication nor the action of a helicase involved in DNA repair.